Contribuição de um modelo sustentável de otimização e de simulação em rede petri p-temporizada nas estratégias de expansão da rede intermodal de transporte de soja do estado do Mato Grosso - Gustavo Rodrigues de Morais (2023)
The production of Brazilian soybean has gained prominence in the world market, generating a revolution in the agribusiness sector. The grain has become one of the main highlights of exports, significantly boosting the national economy, due to its low production costs and the high quality of the product. However, even though it maintains the leadership in the world ranking in this regard, Brazil has lost a competitive advantage in terms of product distribution difficulties due to the limitations of its logistics network. This is one of the most emerging problems in the state of Mato Grosso, the largest producer, and exporter of soy in Brazil. So, this study addresses the intermodal expansion strategies for MT soybeans. To tackle the problem, we propose a sustainable optimization and simulation model in P-timed Petri net directed. The techniques allow locating, dimensioning, and estimating installation costs for transshipment terminals in the state. Then, we can analyze different scenarios for the domestic flow to the main ports, considering the trade-off cost of transport and environmental sustainability. The investigation considers the soybean export database for the year 2021 and the projection for the year 2025. The results of the optimization model indicate a minimum reduction of 20% in CO2 emissions in all analyzed scenarios, keeping the focus on the minimum cost of installing the terminal infrastructure. The stochastic P-timed Petri net simulator solutions point to several alternatives for reducing the cost of transport even considering a 20.6% increase in the amount of soy destined for export from 2021 to 2025. Regarding the explored scenarios, the importance of the EF-170 railroad (ferrogrão) is verified in terms of its impact on reducing CO2 emissions and reducing transport costs for soy destined for export. The applied techniques effectively prove their efficiency as valuable strategic tools in decision-making about expansion projects for the state's intermodal transport network. Thus, we concluded that it is possible to obtain efficient and innovative solutions that combine cost reduction in the soybean logistics system in the state of Mato Grosso with due environmental responsibility. Therefore, it is essential that companies and governments invest in transport intermodality, in order to improve the sector's competitiveness in the international market.